Hybrid CMOS-Memristor based operational transconductance amplifier for high frequency applications. (October 2022) - Sahoo, Satyajeet; Ramana Murthy, G.; Ramesh, S.; Anitha, G.
Abstract: This paper deals with designing an optimized hybrid Operational Transconductance Amplifier (OTA) employing a technique called source degeneration with adaptive biasing that can be used for high frequency applications. This work targets implementation of a simple technique with less number of circuit elements which reduces the die area and power consumption and gives rise to good results. The circuit has been designed to operate with a supply voltage of ±1 V along with a bias current. The linearity which is the major drawback of the conventional Complementary Metal Oxide Semiconductor (CMOS) OTA gets improved with source degeneration technique using a non-CMOS non-volatile memory (so-called memristor). The gain-bandwidth product gets improved for an 80pF load. A biquad OTA-C filter is designed and implemented utilizing the OTA designed in this work as an application example. The realization of a high pass filter has been demonstrated. All the simulations were carried out in the Cadence® Virtuoso environment using 180 nm CMOS technology. Another facet of this paper is the memristor compatibility with the CMOS process technology.